Reader Response of Short Stories by Yulismar on Facebook (Literature Reception Approach) - Syafrial, Syafrial; Syahrani, Rezki Puteri; Fatimah, Nurul (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The Nationâs Literacy Movement [Gerakan Literasi Bangsa (GLB)] which is the implementation of Permendikbud No. 23 Year 2013 started to show responses from teachers and students. It was proved by literacy activities in schools the rise of writers from teachers. One of the teachers implemented literacy movement is Yulismar, a teacher of SMP Negeri 8 Pekanbaru. She used social media (facebook) as the means of literacy activities. This study investigated the reader response using literature reception approach. This study used mixed methods research. The data collection technique was by inventorying all readers from each short story. The findings showed that the most responses were on a short story entitled Surat Rindu untuk Ibu with total 177 readers. Whereas the loyal readers who followed short stories by Yulismar were 71 readers who consisted of 62 female and 9 male. This means that Yulismar, through her work of short stories was successful to build loyal readers. The loyal readers were not only criticized the aspect of the simplicity of the language but also criticized the logical content of the story and touched their consciences.